IN MULTIPLE ATRIOVENTRICULAR BLOCK IN HEART DISEASES, ITS TYPES, OBJECTIVE OBJECTIVE SIGNS OF THE PATIENT, CAUSED DISEASES AND THEIR TREATMENT METHODS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Heart diseases (heart diseases) are a group of pathologies related to the cardiovascular system, manifested by a violation of the normal activity of the heart. Such diseases may be caused by damage to the epicardium, pericardium, myocardium, endocardium, valvular apparatus of the heart, and blood vessels. Heart diseases can be hidden for a long time, without a clinical picture. Along with various tumors, it is one of the main causes of premature death in developed countries today. The continuous operation of the blood circulation system, consisting of the heart and blood vessels, which acts as a pump, is a necessary condition for the normal functioning of the body.